2018
DOI: 10.1101/499368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative analysis of Dupuytren’s disease identifies novel risk locus and reveals a shared genetic etiology with BMI

Abstract: 1Dupuytren's disease is the common inherited tissue-specific fibrotic disorder. It's characterized 2 by progressive and irreversible fibroblastic proliferation affecting the palmar fascia of the hand, 3 with an onset typically in the sixth decade of life. Although genome-wide association studies 4 (GWAS) have identified 24 genomic regions associated with Dupuytren's risk, the biological 5 mechanisms driving signal at these regions remain elusive. We identify potential biological 6 mechanisms for Dupuytren's di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
1
0
0
Order By: Relevance
“…Several epidemiological studies have reported that a high body mass index (BMI) is associated with a lower risk of DD (Gudmundsson et al., 2000; Hacquebord et al., 2017). This association is supported by a recent transcriptome-wide association study, which revealed a negative genetic correlation between BMI and DD risk (Major et al., 2019). However, the causal relationship for this correlation has yet to be explored, and no biological mechanisms have been proposed to explain how high BMI could protect against the development of DD.…”
Section: Introductionsupporting
confidence: 57%
“…Several epidemiological studies have reported that a high body mass index (BMI) is associated with a lower risk of DD (Gudmundsson et al., 2000; Hacquebord et al., 2017). This association is supported by a recent transcriptome-wide association study, which revealed a negative genetic correlation between BMI and DD risk (Major et al., 2019). However, the causal relationship for this correlation has yet to be explored, and no biological mechanisms have been proposed to explain how high BMI could protect against the development of DD.…”
Section: Introductionsupporting
confidence: 57%